Exercise-Induced Cognitive Plasticity, Implications for Mild Cognitive Impairment and Alzheimer’s Disease - Foster, Philip P.; Rosenblatt, Kevin P.; Kuljiš, Rodrigo O. (Frontiers in Neurology, 2011)
Lifestyle factors such as intellectual stimulation, cognitive and social engagement, nutrition, and various types of exercise appear to reduce the risk for common age-associated disorders such as Alzheimer’s disease (AD) and vascular dementia. In fact, many studies have suggested that promoting physical activity can have a protective effect against cognitive deterioration later in life. Slowing or a deterioration of walking speed is associated with a poor performance in tests assessing psychomotor speed and verbal fluency in elderly individuals. Fitness training influences a wide range of cognitive processes, and the largest positive impact observed is for executive (a.k.a. frontal lobe) functions. Studies show that exercise improves additional cognitive functions such as tasks mediated by the hippocampus, and result in major changes in plasticity in the hippocampus. Interestingly, this exercise-induced plasticity is also pronounced in APOE ε4 carriers who express a risk factor for late-onset AD that may modulate the effect of treatments. Based on AD staging by Braak et al., we propose that the effects of exercise occur in two temporo-spatial continua of events. The “inward” continuum from isocortex (neocortex) to entorhinal cortex/hippocampus for amyloidosis and a reciprocal “outward” continuum for neurofibrillary alterations. The exercise-induced hypertrophy of the hippocampus at the core of these continua is evaluated in terms of potential for prevention to stave off neuronal degeneration. Exercise-induced production of growth factors such as the brain-derived neurotrophic factor (BDNF) has been shown to enhance neurogenesis and to play a key role in positive cognitive effects. Insulin-like growth factor (IGF-1) may mediate the exercise-induced response to exercise on BDNF, neurogenesis and cognitive performance. It is also postulated to regulate brain amyloid β (Aβ) levels by increased clearance via the choroid plexus. Growth factors, specifically FGF and IGF-1